An Empirical Study of Dividend Policies in Developing Countries - Chee, Yoong Chuan (2014)
The main objective of this paper is to study dividend payout practices and identify determinants of dividend policies of developing countries in six major regions across the world, which have been receiving less attention compared to that of developed countries. This paper collects panel data of listed firms in 25 developing countries as defined by World Bank, between the years of 2000 and 2011. In examining dividend practices of developing countries, it is found that more than 50 percent of firms in developing countries fall under the categories of “fixed” and “somewhat fixed”, which suggest that firms are paying stable dividends to attract investors. Besides, eight hypotheses were tested using Multiple Regression Analysis and the overall results show that leverage, profitability, risk, growth opportunities, free cash flow, tangibility and firm size are significantly associated with dividend while liquidity has no impact on the dividend policies of the developing countries. In addition, this study also finds that dividend determinants (except growth opportunities) of the developing countries are quite similar to that of the U.S. Generally, the results show that dividend policies of most of the countries are affected by different determinants at different levels of sensitivity, suggesting others country and environmental factors may contribute to the varying determinants in different countries. In a nutshell, this study concludes that there is no universal acceptable dividend theory to explain the dividend behavior of each country.